An orphan crop, the orange-fleshed sweet potato, in West Africa: Can we reposition it? - Abidin, P.E.; Adekambi, S.; Nchor, J.; Koara, I.; Carey, E.E. (2017)
Sweet potato (Ipomoea batatas L.) was not an important crop in Ghana, Burkina Faso and Nigeria, West Africa, in the past decades. An effort has been made to reposition the sweet potato crop in West Africa. Orange-Fleshed Sweet potato (OFSP) cultivar was used as an entry point while properly designing a market-driven approach in the research project, ‘Jumpstarting OFSP in West Africa through diversified markets’. The project was implemented in these three countries in the period of April 2014 throughout March 2017. There is a clear indication that sweet potato is shifted from an orphan crop into a commercial one in these project areas. Obviously, the sweet potato crop has significantly become an important crop among other commercial agricultural commodities in the localities. Additionally, as the OFSP cultivars have already well known for its contribution to food and nutrition security, as well as to a wealth. Hence, the sweet potato crop will give great opportunities to people to improve their livelihood along with healthy life, particularly in the drought-prone regions where the homes of most resourcepoor farmers, and where the sweet potato crop is grown and consumed most. Establishment of various market models evidently played an important role to support this effort.